2012
DOI: 10.1177/0309133312451303
|View full text |Cite
|
Sign up to set email alerts
|

Effects of land use on annual runoff and soil loss in Europe and the Mediterranean

Abstract: The largest currently compiled database of plot runoff and soil loss data in Europe and the Mediterranean was analysed to investigate effects of land use on annual soil loss (SL), annual runoff (R) and annual runoff coefficient (RC). This database comprises 227 plot-measuring sites in Europe and the Mediterranean, with SL for 1056 plots (PL) representing 7024 plot-years (PY) and R for 804 PL representing 5327 PY. Despite large data variability, continental-wide trends are observed. Construction sites have the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
128
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(148 citation statements)
references
References 192 publications
12
128
0
4
Order By: Relevance
“…The analysis of data collected from runoff plots across Europe and the Mediterranean Basin illustrated that runoff coefficients in vineyards (ca. 8%) were similar as those observed in cereal and fallow fields (8.0% and 7.3%), although soil loss was much higher in vineyards (10.8 Mg ha −1 y −1 ) than in arable and fallow land (6.5 and 5.8 Mg ha −1 y −1 ) [9]. However, the mean standard deviation (sd) of the soil erosion rates in vineyards from the Mediterranean zone (sd = 27.4 Mg ha −1 y −1 ) and the rest of Europe (sd = 26.0 Mg ha −1 y −1 ) is very high, and thus, the spatial variability of soil loss in this crop is also high [5].…”
Section: Introductionsupporting
confidence: 80%
“…The analysis of data collected from runoff plots across Europe and the Mediterranean Basin illustrated that runoff coefficients in vineyards (ca. 8%) were similar as those observed in cereal and fallow fields (8.0% and 7.3%), although soil loss was much higher in vineyards (10.8 Mg ha −1 y −1 ) than in arable and fallow land (6.5 and 5.8 Mg ha −1 y −1 ) [9]. However, the mean standard deviation (sd) of the soil erosion rates in vineyards from the Mediterranean zone (sd = 27.4 Mg ha −1 y −1 ) and the rest of Europe (sd = 26.0 Mg ha −1 y −1 ) is very high, and thus, the spatial variability of soil loss in this crop is also high [5].…”
Section: Introductionsupporting
confidence: 80%
“…Soil erosion rates are generally different for various land cover and land use types [25,26]. The 2014 land cover and land use map for Uganda (Figure 3) acquired from the Regional Center for Mapping of Resources for Development (RCMRD) Land Cover Viewer database [17] was used to separate erosion and non-erosion prone areas and to assess the rates of soil erosion risk for different land cover and land use types.…”
Section: Land Cover and Land Usementioning
confidence: 99%
“…Moreover, the seasonal variation of rainfall erosivity is not considered, which restricts using of the erosivity map for erosion prediction in many cases. Maetens et al (2012) conducted studies in Europe and Mediterranean by reviewing data from 227 stations and 1056 soil erosion plots to predict the effect of land use on annual soil erosion, annual runoff and annual runoff coefficient. They concluded that the soil loss does not correlate better with erosivity indices than with total rainfall.…”
Section: Rainfall Erosivity Factormentioning
confidence: 99%